2007
DOI: 10.2172/912469
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion Testing of Borated Stainless Steel Alloys

Abstract: The Department of Energy Office of Civilian Radioactive Waste Management has recommended borated stainless steel manufactured to the requirements of ASTM A 887-89, Grade A, UNS S30464, to be the material used for the fabrication of the fuel basket internals of the preliminary transportation, aging, and disposal canister system preliminary design. The long-term corrosion resistance performance of this class of borated materials must be verified when exposed to expected YMP repository conditions after a waste pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Similarly to the non-borates stainless steels, there is significantly less data available on the corrosion of borated stainless steel under anoxic conditions. Lister et al (2008) measured the corrosion rate of three borated stainless steel 304B alloys with varying boron content at 60 °C. Samples were creviced, and potentiostatic tests were performed in anoxic conditions and in an acidic environment.…”
Section: Corrosion Of Borated Stainless Steel Under Anoxic Conditionsmentioning
confidence: 99%
“…Similarly to the non-borates stainless steels, there is significantly less data available on the corrosion of borated stainless steel under anoxic conditions. Lister et al (2008) measured the corrosion rate of three borated stainless steel 304B alloys with varying boron content at 60 °C. Samples were creviced, and potentiostatic tests were performed in anoxic conditions and in an acidic environment.…”
Section: Corrosion Of Borated Stainless Steel Under Anoxic Conditionsmentioning
confidence: 99%
“…The measured corrosion rate increased with increasing boron content. The average corrosion rates were 0.221±0.070 µm yr -1 for 304B4 (1.17 % B), 0.427±0.132 µm yr -1 for 304B5 (1.32 % B), and 0.464±0.100 µm yr -1 for 304B6 (1.69 % B) (Lister et al 2008). The uniform corrosion rates for borated stainless steels are summarized in Table B-2.…”
Section: Corrosion Of Borated Stainless Steel Under Anoxic Conditionsmentioning
confidence: 96%
“…Uniform Corrosion -Lister et al (2007) performed electrochemical corrosion testing of borated stainless steel alloys and measured a uniform corrosion rate of 0.0176-0.0371 µm yr -1 at 60°C in an aerated simulated in-package solution. The authors state that the results are indicative of short-term corrosion rates and that a longer-term test would be required for a comprehensive prediction of borated stainless steel behavior in a waste package.…”
Section: Corrosion Of Borated Stainless Steel Under Oxic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While other elements can act as neutron absorbers, boron and gadolinium are effective and are easily incorporated into steels. Previous corrosion studies with 304B SS (Lister et al 2007) using very dilute test solutions considered relevant to the Yucca Mountain Project, indicated that it performed well under those conditions, corroding at less than 0.05 µm yr -1 . However, repository conditions in a clay or granite repository could be considerably different than those tested.…”
Section: Neutron Absorber Materialsmentioning
confidence: 99%